A Cost Analysis of Single-Stage Bilateral versus Two-Stage Direct Anterior Total Hip Arthroplasty. Issue 1 (January 2016) - Martin, Glynn R.; Marsh, Jacquelyn D.; Vasarhelyi, Edward M.; Howard, Jamie L.; Lanting, Brent A.
Purpose: The potential cost savings of single-stage bilateral total hip arthroplasty (THA) are unclear, and the risks associated with it are not well defined. We sought to compare the costs and perioperative complications of single-stage bilateral THA via the direct anterior approach (DAA) to a two-stage bilateral protocol. Methods: We retrospectively reviewed patients who underwent a single- stage bilateral DAA THA and compared them to a two-stage THA group. We conducted a cost analysis from both the hospital perspective and the Ministry of Health (MOH) perspective. Results: 24 patients were included in this study. The 2 groups were similar in age (58.9 vs 63.9 yrs), height (169.2 vs 170.9 cm), weight (80.2 vs 78.6 kg), BMI (27.9 vs 26.3 kg/m 2 ), ASA score (2.2 vs 2.2), and CCI score (2.3 vs 2.9). The mean cost per patient from the hospital perspective for the single-stage group was $10, 728.13 (SD = 621.46) compared to $12, 670.63 (SD = 519.72) for the two-stage group (Mean Difference = $1, 942.50, 95% CI = $1, 457.49 to $2, 427.51, p<0.001). Similarly, from the MOH perspective, the cost for the single-stage group was $12, 552.34 (SD = 644.93) compared to $14, 740.58 (SD = 598.07) for the two-stage group (Mean Difference = $2, 188.24, 95% CI = $1, 661.67 to $2, 714.81, p<0.001). There were no significant differences in complication rate between groups. The largest percent of total cost savings from a hospital perspective was attributed to cost of operating room staff and OR set-up (55%). Conclusions: Our results suggest that single-stage bilateral DAA THA results in significant cost savings compared to two-stage DAA THA.